Problem of organized crime in Perú: contemporary phase - Alexander Shinkarenko (Ибероамериканские тетради, 2016)
The article deals with the problems of the organized crime in Perú and its causes. Are issued the problems of narcotraﬁc, corruption, violence and such new types of crime as ciberfraud.